TINJAUAN YURIDIS AKTA PERDAMAIAN YANG DILAKUKAN PARA PIHAK DI HADAPAN NOTARIS - RAZIKIN, ABDUL KHAIR ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study discussed the Judicial Review Act for Peace in the Outer Court and its implementation. Authority of the notary deed in making peace, and peace are made in the deed before a notary who has the legal power as a court decision which has had permanent legal force. The research was conducted by the normative legal research through literature study using a qualitative approach to data analysis is inductive, which is a scientific activity related to analysis and construction are carried out methodological, systematic and consistent. Results showed that, (1) Notary deed authorities in making peace, as his position as a public official authorized to make an authentic deed. Authentic deeds as proof of the strongest and fullest play an important role in any legal relationship in public life. Deed for the desired peace is made by interested parties to ensure the rights and obligations of the parties for the sake of certainty, order, and legal protection for interested parties. And in the process of peace settlement of disputes with the deed is written evidence, the strongest and fullest and contribute significantly to the settlement of disputes quickly and cheaply, (2) Peace Efforts can be made either before the trial court made, or after the trial court held both within and outside the court. Peace notarial deed have permanent legal force, and force eksekutorial with the determination issued by the Chief District Court contains a command execution so that peace can be executed deed. Deed of peace, made before Notary has a legitimate legal position on court decisions and as a means of proving complete. Notarized deed of peace have permanent legal force, and force eksekutorial with the determination issued by the Chief District Court contains a command execution so that peace can be executed deed.